Coated pharmaceutical composition and method for preparing the same

By applying a metal oxide layer on the drug particles, the stability of the amorphous drug API with poor solubility is solved, the bioavailability and stability of the manufacturing process are improved, and the efficient storage and fluidity of the drug are improved.

CN115697310BActive Publication Date: 2025-01-10APPLIED MATERIALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180035116.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-05
Filing Date
2021-06-07
Publication Date
2025-01-10
Estimated Expiration
2041-06-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively stabilize and store amorphous drug APIs with poor solubility, resulting in low bioavailability and easy crystallization, affecting the stability and manufacturing process of the drug.

Method used

A metal oxide layer is applied to the drug particles by atomic layer deposition technology to form an encapsulated structure, and amorphous solid dispersion is prepared by hot melt extrusion or spray-drying, which improves the glass transition temperature and fluidity of the drug and inhibits the occurrence of crystallization.

Benefits of technology

It significantly improves the stability and bioavailability of the drug, extends the holding time of the amorphous state, reduces agglomeration and hygroscopicity, improves the compressibility and fluidity of the drug, and improves the quality of the drug products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115697310B_ABST
    Figure CN115697310B_ABST
Patent Text Reader

Abstract

A pharmaceutical composition containing metal oxide-coated particles, the pharmaceutical composition comprising 1) an amorphous solid dispersion (ASD) core containing an active pharmaceutical ingredient (API) and a polymer; and 2) a metal oxide coating, and a method of making the metal oxide-coated particles by atomic layer deposition (ALD). The metal oxide-coated particles are useful because the metal oxide-coated particles prevent the ASD from crystallizing and help maintain the ASD in an amorphous form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to coated pharmaceutical compositions and methods of making coated pharmaceutical compositions. Background Art

[0002] For the pharmaceutical industry, developing improved formulations of active pharmaceutical ingredients (APIs) is of great interest. Formulations can affect the stability and bioavailability of APIs, as well as other properties. Formulations can also affect various aspects of drug product (DP) manufacturing, such as the ease and safety of the manufacturing process.

[0003] Many APIs have poor solubility. Among approved drugs, about 40% contain poorly soluble APIs. The percentage of poorly soluble compounds in compounds under development is much higher. Poor solubility leads to poor bioavailability. APIs in amorphous form are generally more soluble than crystalline forms. Therefore, it is often desirable to produce drug formulations in which the API is amorphous rather than crystalline and remains amorphous during storage. Amorphous solid dispersions (ASD) of APIs, usually in polymers, can stabilize the amorphous form of APIs to prevent crystallization. ASD has advantages in supersaturated solubility, dissolution, and improved bioavailability. Compared with the crystalline form of API, ASD is thermodynamically unstable. However, the polymer matrix, for example, inhibits recrystallization by presenting a higher viscosity below the glass transition temperature (Tg) or by drug-polymer interactions. ASD is most often produced by hot melt extrusion, spray drying, or anti-solvent pads. Ideally, the ASD will be kinetically stable during the expected shelf life of the ASD, but will mostly return to the crystalline form. Exposure to high humidity or high temperature significantly increases the flowability of the API in the ASD and reduces the ability of the polymer to inhibit recrystallization.Crystallization of the API in the ASD can occur via both bulk crystallization and surface crystallization. Summary of the invention

[0004] The present invention describes a method for preparing a pharmaceutical composition comprising coated particles, which coated particles include an amorphous solid dispersion of an active pharmaceutical ingredient (ASD particles) encapsulated by one or more metal oxide layers, the method comprising the following sequential steps: (a) providing particles of an amorphous solid dispersion comprising an active pharmaceutical ingredient and a polymer; (b) performing atomic layer deposition to apply a metal oxide layer to the particles of the amorphous solid dispersion comprising an active pharmaceutical ingredient and a polymer, thereby preparing coated particles comprising an active pharmaceutical ingredient encapsulated by one or more metal oxide layers; and (c) treating the coated particles to prepare a pharmaceutical composition.

[0005] In various embodiments: the particles are at least 50%, 60%, 65%, 70% wt / wt drug; the particles have a D50 of 0.1 μm to 200 μm (e.g., 0.1 μm to 10 μm or 0.1 μm to 5 μm) based on a spatial average; the particles have a D90 of 200 μm to 2000 μm based on a spatial average; the glass transition temperature of the active pharmaceutical ingredient in the coated particles is higher than the glass transition temperature of the active pharmaceutical ingredient in the provided particles; the polymer is selected from the group consisting of: hydroxypropyl methylcellulose, hydroxypropyl methylcellulose acetate succinate (HPMCAS), and polyvinyl pyrrolidone (PVP), polyvinyl pyrrolidone / vinyl acetate (PVPVA), polyethylene glycol (PEG), polyacrylate and polymethacrylate; step (a) comprises preparing the ASD particles by hot melt extrusion; step (a) comprises preparing the ASD particles by spray drying;

[0006] In various embodiments: the step of performing atomic layer deposition comprises:

[0007] (b1) loading particles containing the drug into a reactor;

[0008] (b2) applying a vapor or gaseous metal precursor to the particles in the reactor;

[0009] (b3) performing one or more pump-purge cycles of the reactor using an inert gas;

[0010] (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and

[0011] (b5) performing one or more pump-purge cycles of the reactor using an inert gas.

[0012] In various embodiments, steps (b2) to (b5) are performed two or more times before performing step (c) to increase the total thickness of the metal oxide layer; the reactor contents are stirred before and / or during step (a); the reactor pressure is stabilized after step (b1), step (b2), and / or step (b4); the reactor contents are stirred before and / or during step (b1), step (b3), and / or step (b5); a subset of the vapor or gaseous contents is pumped out before step (b3) and / or step (b5); the metal oxide layer has a thickness in the range of 0.1 nm to 100 nm (e.g., 0.1 nm to 50 nm); step (c) comprises combining the coated particles with one or more pharmaceutically acceptable excipients; the metal oxide is selected from the group consisting of: zinc oxide, aluminum oxide, silicon oxide, and titanium oxide; step (b) occurs at a temperature between 25°C and 50°C; step (b) occurs at a temperature between 25°C and 100°C.

[0013] Also described are pharmaceutical compositions comprising coated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, the pharmaceutical composition being prepared by a process comprising the following sequential steps:

[0014] (a) providing particles of an amorphous solid dispersion comprising an active pharmaceutical ingredient and a polymer;

[0015] (b) performing atomic layer deposition to apply a metal oxide layer to particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient and a polymer, thereby preparing coated particles comprising the active pharmaceutical ingredient encapsulated by one or more metal oxide layers; and

[0016] (c) processing the coated particles to prepare a pharmaceutical composition.

[0017] In various embodiments of the composition, the step of performing atomic layer deposition comprises:

[0018] (b1) loading particles containing the drug into a reactor;

[0019] (b2) applying a vapor or gaseous metal precursor to the particles in the reactor;

[0020] (b3) performing one or more pump-purge cycles of the reactor using an inert gas;

[0021] (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and

[0022] (b5) performing one or more pump-purge cycles of the reactor using an inert gas.

[0023] In various embodiments of the composition: the particles are at least 50%, 60%, 65%, 70% wt / wt drug; the particles have a D50 of 0.1 μm to 200 μm (e.g., 0.1 μm to 10 μm or 0.1 μm to 5 μm) based on a spatial average; the particles have a D90 of 200 μm to 2000 μm based on a spatial average; the glass transition temperature of the active pharmaceutical ingredient in the coated particles is higher than the glass transition temperature of the active pharmaceutical ingredient in the provided particles; the polymer is selected from the group consisting of: hydroxypropyl methylcellulose, hydroxypropyl methylcellulose acetate succinate, and polyvinyl pyrrolidone, polyvinyl pyrrolidone / vinyl acetate, polyethylene glycol (PEG), polyacrylate and polymethacrylate; step (a) comprises preparing the ASD particles by hot melt extrusion; step (a) comprises preparing the ASD particles by spray drying;

[0024] In various embodiments: the step of performing atomic layer deposition comprises:

[0025] (b1) loading particles containing the drug into a reactor;

[0026] (b2) applying a vapor or gaseous metal precursor to the particles in the reactor;

[0027] (b3) performing one or more pump-purge cycles of the reactor using an inert gas;

[0028] (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and

[0029] (b5) performing one or more pump-purge cycles of the reactor using an inert gas.

[0030] In various embodiments, steps (b2) to (b5) are performed two or more times before performing step (c) to increase the total thickness of the metal oxide layer; the reactor contents are stirred before and / or during step (a); the reactor pressure is stabilized after step (b1), step (b2), and / or step (b4); the reactor contents are stirred before and / or during step (b1), step (b3), and / or step (b5); a subset of the vapor or gaseous contents is pumped out before step (b3) and / or step (b5); the metal oxide layer has a thickness in the range of 0.1 nm to 100 nm; step (c) comprises combining the coated particles with one or more pharmaceutically acceptable excipients; the metal oxide is selected from the group consisting of: zinc oxide, aluminum oxide, silicon oxide, and titanium oxide; step (b) occurs at a temperature between 25°C and 50°C; step (b) occurs at a temperature between 25°C and 50°C.

[0031] Prior to coating, the particles may have a median particle size based on a spatial average of between 0.01 μm and 1000 μm.

[0032] The pharmaceutical composition may be removed from the reactor and mixed with one or more pharmaceutically acceptable diluents or carriers.

[0033] Prior to coating, the particles may consist essentially of the API.

[0034] The one or more oxide materials include silicon oxide and various metal oxides including aluminum oxide, titanium oxide, iron oxide, gallium oxide, magnesium oxide, zinc oxide, niobium oxide, hafnium oxide, tantalum oxide, lanthanum oxide, and / or zirconium dioxide.

[0035] The oxidizing agent may be selected from the group of water, ozone, and organic peroxides.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. Methods and materials for use in the present invention are described herein; other suitable methods and materials known in the art may also be used. The materials, methods, and examples are illustrative only and are not intended to be limiting.

[0037] Other features and advantages of the invention will be apparent from the following detailed description and drawings, and from the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a schematic diagram of a rotating reactor for ALD coating of particles (eg, ASD particles).

[0039] Figure 2 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles.

[0040] Figure 3 Depicted are the results of differential scanning calorimetry (DSC) analysis of uncoated and metal oxide coated ASD particles.

[0041] Figure 4 Scanning electron microscope images of uncoated and metal oxide coated ASD particles are depicted.

[0042] Figure 5 Depicted are the results of bulk density and tap density analysis of uncoated and metal oxide coated ASD particles.

[0043] Figure 6 Depicted are the results of moisture sorption analysis of uncoated and metal oxide coated ASD particles.

[0044] Figure 7 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles under accelerated stability testing.

[0045] Figure 8 Depicted are the results of x-ray diffraction analysis of uncoated ASD particles under accelerated stability testing.

[0046] Fig. 9 Depicted are the results of measured differential scanning calorimetry (DSC) analysis of uncoated and metal oxide coated ASD particles under accelerated stability testing.

[0047] FIG. 10A to FIG. 10B Depicted are scanning electron microscope images of uncoated and metal oxide coated ASD particles under accelerated stability testing.

[0048] FIG. 11A to FIG. 11B Depicted are scanning electron microscope images of uncoated and metal oxide coated ASD particles under accelerated stability testing.

[0049] Fig.12 Depicted are the results of dissolution analysis of uncoated and metal oxide coated ASD particles under accelerated stability testing.

[0050] Fig.13 Depicted are the results of dissolution analysis of uncoated and metal oxide coated ASD particles under accelerated stability testing.

[0051] Fig.14 Depicted are the appearance of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for 8 months at 40°C and 75% relative humidity.

[0052] Fig.15 Depicted are scanning electron microscopy images of uncoated and metal oxide coated 50% DL (drug loaded) ASD particles (alumina / ezetimibe / HPMCAS) after storage at 40°C and 75% relative humidity for different time periods (12 days, 47 days, 210 days, 240 days and 270 days).

[0053] Fig.16 Depicted are scanning electron microscopy images of uncoated and metal oxide coated 70% DL ASD particles (alumina / ezetimibe / HPMCAS) after storage at 40°C and 75% relative humidity for different time periods (12 days, 61 days, 180 days, 210 days, 240 days and 270 days).

[0054] Fig.17 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for 9 months at 40°C and 75% relative humidity. Fig.17 As shown, there is about 25% crystallinity for the uncoated ASD with 50% API loading, about 50% crystallinity for the uncoated ASD with 70% API loading, and no crystallinity for most of the coated samples.

[0055] Fig.18 Depicted are the results of release studies of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for various durations at 40°C and 75% relative humidity.

[0056] Fig.19Depicted are scanning electron microscopy images of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for one year at 40°C and 75% relative humidity.

[0057] Fig. 20 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for one year at 40°C and 75% relative humidity.

[0058] Fig.21A and Fig. 21B Depicted are the results of dissolution analysis of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for various durations at 40°C and 75% relative humidity. Fig. 21C Depicted are the results of dissolution analysis of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for one year at room temperature or 40°C and 75% relative humidity.

[0059] Fig. 22 Depicted are SEM and TEM / FIB cross-sectional images of metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading.

[0060] Fig.23 Depicted are powder flow characterizations of uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading.

[0061] Fig.24 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading.

[0062] Fig.25A and Fig.25B Depicted are the results of FTIR analysis of uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading.

[0063] FIG. 26A to FIG. 26C Depicted are coating thickness, oxide content, SEM images, and TEM images of uncoated and metal oxide coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading. Fig.26B SEM images of uncoated ASD (EP50-15), thinly coated ASD (B3-284A), and thickly coated ASD (B3-284B) are depicted. Fig.26CDepicted is a TEM image of a cross section of uncoated ASD (EP50-15).

[0064] Fig. 27 Moisture sorption of uncoated and metal oxide coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading at 40°C is depicted.

[0065] Fig.28 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading stored in capped glass vials at 40°C and 43% relative humidity for 4 weeks.

[0066] Fig.29 Depicted are scanning electron microscopy images of uncoated and metal oxide coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading stored in open bottles at 40°C and 43% relative humidity for 4 weeks.

[0067] Fig. 30A Depicted are the determination of nifedipine and water content of freshly prepared various uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading. Fig. 30B TEM images of cross sections of 50% and 70% coated DL ASD particles are depicted.

[0068] Fig.31 Depicted are the appearance of freshly prepared uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading.

[0069] FIG. 32A to FIG. 32F Depicted are the results of x-ray diffraction analysis of PVP, nifedipine, uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading.

[0070] FIG. 33A to FIG. 33D Depicted are assays, moisture sorption, and impurity analysis of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored in capped amber glass bottles, capped HDPE bottles sealed with induction, or open HDPE bottles without caps.

[0071] Fig.34Depicted are the appearance of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored for various durations in open HDPE bottles without caps at 40°C and 75% relative humidity.

[0072] Fig.35 Depicted are the appearance of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored for various durations in induction sealed HDPE bottles with caps.

[0073] Fig.36 Depicted are the appearance of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored for various durations in capped amber bottles.

[0074] Fig.37 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored in capped amber bottles at 25°C and 60% relative humidity for 3 months.

[0075] Fig.38 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored in capped, induction sealed HDPE bottles at 40°C and 75% relative humidity for 3 months.

[0076] Fig.39 Depicted are the results of x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored in open HDPE bottles without caps for 3 months at 40°C and 75% relative humidity.

[0077] FIG. 40A to FIG. 40CDepicted are scanning electron microscopy images of uncoated and metal oxide coated ASD particles (alumina / nifedipine / HPMCAS) with 50% (SF20000521) and 70% (SF20000611) drug loadings freshly prepared, after 2 months of storage, or after 3 months of storage in open HDPE bottles without caps at 40°C and 75% relative humidity. Fig.40A An image of an uncoated ASD is depicted, and complete gelation and crystallization are observed. Fig.40B Depicted is an ASD with 50% drug loading coated and Fig.40C Depicted is a coated ASD with 70% drug loading.After 3 months storage at 40°C and 75% relative humidity, no crystallization was observed for both the coated ASDs with 50% or 70% drug loading. DETAILED DESCRIPTION

[0078] The present disclosure provides a method for preparing a pharmaceutical composition comprising particles of an amorphous solid dispersion (ASD) coated with one or more layers of an oxide (e.g., a metal oxide) ("ASD particles"). The coating layer is conformal and has a controlled thickness. The coating process described herein can provide ASD particles in which the crystallization of the API is significantly inhibited. Importantly, the coating can reduce the need for a high weight percentage of the polymer in the ASD. This allows the preparation of ASD particles with high drug loading. For example, the ASD particles can have a drug loading of 50%, 60%, or 70% wt / wt. This high drug loading of the particles, together with the relative thickness of the oxide coating, allows the preparation of a pharmaceutical composition. Because the coating is relatively thin, a drug product with a high drug loading can be produced. For example, the metal oxide layer can have a thickness in the range of 0.1 nm to 100 nm. In addition, the oxide coating can improve the properties of the ASD particles related to various aspects of drug product manufacturing. For example, compared to otherwise identical uncoated ASD particles, the coated ASD particles can have improved flowability and compressibility. Furthermore, the coated ASD particles may have a reduced tendency to agglomerate compared to otherwise identical uncoated ASD particles.Finally, because multiple coatings may be applied in the same reactor, there are benefits with respect to cost and ease of manufacturing.

[0079] drug

[0080] The term "drug" in its broadest sense includes all small molecule (e.g., non-biological) APIs, particularly APIs that are organic molecules. The drug may be selected from the group consisting of analgesics, anesthetics, anti-inflammatory agents, anthelmintics, antiarrhythmic agents, antiasthmatic agents, antibiotics, anticancer agents, anticoagulants, antidepressants, antidiabetics, antiepileptics, antihistamines, antitussives, antihypertensives, antimuscarinics, antimycobacterials, antineoplastics, antioxidants, antipyretics, immunosuppressants, immunostimulants, antithyroid agents, antivirals, anxiolytics, sedatives, hypnotics, neuroleptics, astringents, antibacterials, beta-adrenergic receptor blockers, blood products, blood substitutes , bronchodilators, buffers, cardiac inotropes, chemotherapeutic agents, contrast agents, corticosteroids, cough suppressants, expectorants, mucolytics, diuretics, dopaminergic, antiparkinsonian agents, free radical scavengers, growth factors, hemostatics, immunologic agents, lipid modulators, muscle relaxants, parasympathomimetics, parathyroid calcitonin, bisphosphonates, prostaglandins, radiopharmaceuticals, hormones, sex hormones, antiallergic agents, appetite stimulants, appetite suppressants, steroids, sympathomimetics, thyroid agents, vaccines, vasodilators, and xanthines.

[0081] Exemplary types of small molecule drugs include, but are not limited to, acetaminophen, clarithromycin, azithromycin, ibuprofen, fluticasone propionate, salmeterol, pazopanib hydrochloride, palbociclib, and amoxicillin-clavulanate potassium.

[0082] Metal oxide materials

[0083] The term "metal oxide material" in its broadest sense includes all materials formed by the reaction of an element considered to be a metal or metalloid with an oxygen-based oxidant. Exemplary metal oxide materials include, but are not limited to, aluminum oxide, titanium dioxide, iron oxide, gallium oxide, magnesium oxide, zinc oxide, niobium oxide, hafnium oxide, tantalum oxide, lanthanum oxide, and zirconium dioxide. Silicon oxide is an example of a metal oxide produced by the reaction between a metalloid and an oxygen-based oxidant. Exemplary oxides include, but are not limited to, water, ozone, and inorganic peroxides.

[0084] Atomic Layer Deposition (ALD)

[0085] Atomic layer deposition is a thin film deposition technique in which the sequential addition of self-limiting monolayers of elements or compounds allows the deposition of films with thickness and uniformity controlled at the level of atomic or molecular monolayers. Self-limiting means that only a single atomic layer is formed at a time, and subsequent processing steps are required to regenerate the surface and allow further deposition.

[0086] Reactor system

[0087] The term "reactor system" in its broadest sense includes all systems that can be used to perform ALD. Exemplary reactor systems are Figure 1 and described further below.

[0088] Figure 1 A reactor system 10 for performing coating of particles with a thin film coating is shown. The reactor system 10 can perform ALD coating. The reactor system 10 allows ALD coating to be performed at higher (above 50°C, e.g., 50-100°C or higher) or lower processing temperatures (e.g., below 50°C, e.g., at or below 35°C). For example, the reactor system 10 can form a thin film metal oxide on the particles by ALD primarily at a temperature of 22 to 35°C (e.g., 25 to 35°C, 25 to 30°C, or 30 to 35°C). Typically, the particles can be kept or maintained at such a temperature. This can be achieved by keeping or maintaining the inner surface of the reactant gas and / or the reactor chamber (e.g., chamber 20 and drum 40 discussed below) at such a temperature.

[0089] Again, in the case of an ALD process, the reactor system 10 includes a fixed vacuum chamber 20 coupled to a vacuum pump 24 via a vacuum line 22. The vacuum pump 24 may be an industrial vacuum pump sufficient to establish a pressure of less than 1 Torr (e.g., 1 to 100 mTorr, e.g., 50 mTorr). The vacuum pump 24 allows the chamber 20 to be maintained at a desired pressure and allows for the removal of reaction byproducts and unreacted process gases.

[0090] In operation, the reactor 10 performs an ALD thin film coating process by introducing a gaseous precursor of the coating into the chamber 20. The gaseous precursors are alternately added to the reactor. This allows the ALD process to be a solvent-free process. The half-reaction of the ALD process is self-limiting, which can provide angstrom-level control of the deposition. In addition, the ALD reaction can be performed under low temperature conditions, such as below 50°C, for example, below 35°C.

[0091] The chamber 20 is also coupled to a chemical delivery system 30. The chemical delivery chamber 30 includes three or more gas sources 32a, 32b, 32c coupled to the vacuum chamber 20 via corresponding delivery tubes 34a, 34b, 34c and controllable valves 36a, 36b, 36c. The chemical delivery system 30 may include a combination of flow restrictors, gas flow controllers, pressure sensors, and ultrasonic flow meters to provide controllable flow rates of various gases into the chamber 20. The chemical delivery system 30 may also include one or more temperature control components, such as heat exchangers, resistive heaters, heat lamps, etc., for heating or cooling the various gases before they flow into the chamber 20. Although Figure 1Separate gas lines are shown extending in parallel with the chambers of each gas source, and two or more gas lines may be connected, for example, by one or more three-way valves, before the combined line reaches the chamber 20. In addition, although Figure 1 Three gas sources are shown, and using four gas sources can achieve in situ formation of a laminate structure with alternating layers of two different metal oxides.

[0092] The two gas sources provide two chemically different gaseous reactants for the coating process to the chamber 20. Suitable reactants for the ALD method include any one or combination of the following: monomer vapor, metal organics, metal halides, oxidants (such as ozone or water vapor), and polymer or nanoparticle aerosols (dry or wet). For example, the first gas source 32a can provide gaseous trimethylaluminum (TMA) or titanium tetrachloride (TiCl 4 ), and the second gas source 32b can provide water vapor.

[0093] One of the gas sources may provide a purge gas. In particular, a third gas source may provide a gas that is chemically inert to the reactants, coating, and particles being processed. For example, the purge gas may be N 2 , or an inert gas such as argon.

[0094] A rotatable coating drum 40 is held inside the chamber 20. The drum 40 may be connected via a drive shaft 42 that extends through a sealed port in the side wall of the chamber 20 to a motor 44. The motor 44 may rotate the drum at a speed of 1 to 100 rpm. Alternatively, the drum may be directly connected to a vacuum source through a rotary joint.

[0095] The particles to be coated (illustrated as a particle bed 50) are placed in the interior space 46 of the drum 40. The drum 40 and chamber 20 may include sealable ports (not shown) to allow particles to be placed into and removed from the drum 40.

[0096] The body of the drum 40 is provided by one or more of a porous material, a solid metal, and a perforated metal. The holes passing through the cylindrical side wall of the drum 40 may have a size of 10 μm.

[0097] In operation, as the drum 40 rotates, one of the gases flows from the chemical delivery system 30 into the chamber 20. A combination of pores (1 to 100 μm), holes (0.1 to 10 mm), or large openings in the coating drum 40 is used to confine the particles in the coating drum 40 while allowing rapid delivery of precursor chemicals and pumping of byproducts or unreacted materials. Due to the holes in the drum 40, the gas can flow between the outside of the drum 40 (i.e., the reactor chamber 20) and the inside of the drum 40. In addition, the rotation of the drum 40 stirs the particles to keep the particles separated, thereby ensuring that a large surface area of ​​the particles remains exposed. This allows for rapid, uniform interaction of the particle surface with the process gas.

[0098] In some embodiments, one or more temperature control components are integrated into the drum 40 to allow control of the temperature of the drum 40. For example, a resistive heater, thermoelectric cooler, or other component may be in or on the sidewall of the drum 40.

[0099] The reactor system 10 also includes a controller 60 coupled to various controllable components (e.g., vacuum pump 24, gas distribution system 30, motor 44, temperature control system, etc.) to control the operation of the reactor system 10. The controller 60 may also be coupled to various sensors, such as pressure sensors, flow meters, etc., to provide closed-loop control of the gas pressure in the chamber 20.

[0100] In general, the controller 60 can operate the reactor system 10 according to a "recipe". The recipe specifies the operating values ​​for each controllable element that vary over time. For example, the recipe can specify the duration of operation of the vacuum pump 24, the time and flow rate of each gas source 32a, 32b, 32c, the rotation rate of the motor 44, etc. The controller 60 can receive the recipe as computer-readable data (e.g., stored on a non-transitory computer-readable medium).

[0101] The controller 60 and other computing devices of the system described herein can be implemented in a digital electronic circuit system, or in computer software, firmware, or hardware. For example, the controller may include a processor for executing a computer program stored in a computer program product (e.g., in a non-temporary machine-readable storage medium). Such a computer program (also referred to as a program, software, software application, or code) can be written in any form of programmable language, including a compiled or interpreted language, and such a computer program can be deployed in any form, including as a stand-alone program or as a module, component, subroutine, or other unit suitable for use in a computing environment. In some embodiments, the controller 60 is a general-purpose programmable computer. In some embodiments, the controller can be implemented using a dedicated logic circuit, for example, an FPGA (field programmable gate array) or an ASIC (application-specific integrated circuit).

[0102] operate

[0103] Initially, particles are loaded into drum 40 in reactor system 10. The particles may have a solid core containing a drug (e.g., one of the drugs discussed above). Once any inlets and outlets are sealed, controller 60 operates reactor system 10 according to a manufacturing method to form a thin film metal oxide layer on the particles.

[0104] Specifically, two reactant gases are alternately supplied to chamber 20, and the step of supplying reactant gas is followed by a purge cycle in which an inert gas is supplied to chamber 20 to exhaust the reactant gas and byproducts used in the previous step. In addition, one or more gases (e.g., reactant gas and / or inert gas) can be supplied in a pulsed manner, in which chamber 20 is filled with gas to a specified pressure, a delay time is allowed to pass, and the chamber is evacuated by vacuum pump 24 before the next pulse begins.

[0105] Specifically, the controller 60 may operate the reactor system 10 as follows.

[0106] In the first reactant half-cycle, while the motor 44 rotates the drum 40 to agitate the particles 50:

[0107] i) Operate the gas distribution system 30 to flow a first reactant gas (eg, TMA) from the source 32a into the chamber 20 until a first specified pressure is achieved. The specified pressure may be 0.1 Torr to half the saturation pressure of the reactant gas.

[0108] ii) The flow of the first reactant is paused and a specified delay time is allowed to elapse, for example as measured by a timer in the controller. This allows the first reactant to flow through the particle bed in the drum 40 and react with the surface of the particles 50 inside the drum 40.

[0109] iii) The vacuum pump 50 evacuates the chamber 20, for example, to a pressure below 1 Torr, for example, to 1 to 100 mTorr, for example, 50 mTorr.

[0110] These steps (i) to (iii) may be repeated a number of times set by the production method, for example, two to ten times, for example, six times.

[0111] Next, in the first purification cycle, as the motor 44 rotates the drum to agitate the particles 50:

[0112] iv) operating the gas distribution system 30 to allow the inert gas (e.g., N 2 ) flows from source 32c into chamber 20 until a second specified pressure is achieved. The second specified pressure may be 1 to 100 Torr.

[0113] v) The flow of inert gas is suspended and a specified delay time is allowed to elapse, for example as measured by a timer in the controller. This allows the inert gas to flow through the holes in the drum 40 and diffuse through the particles 50 to replace the reactant gas and any vapor byproducts.

[0114] vi) The vacuum pump 50 evacuates the chamber 20, for example, to a pressure below 1 Torr, for example, to 1 to 500 mTorr, for example, 50 mTorr.

[0115] These steps (iv) to (vi) may be repeated a number of times set by the production method, for example, six to twenty times, for example, sixteen times.

[0116] In the second reactant half-cycle, while the motor 44 rotates the drum 40 to agitate the particles 50:

[0117] vii) operating the gas distribution system 30 to flow the second reactant gas (eg, H2O) from the source 32a into the chamber 20 until a third specified pressure is achieved. The third pressure may be 0.1 Torr to half of the saturation pressure of the reactant gas.

[0118] viii) The flow of the second reactant is paused and a specified delay time is allowed to elapse, for example, as measured by a timer in the controller. This allows the second reactant to flow through the holes in the drum 40 and react with the surface of the particles 50 inside the drum 40.

[0119] ix) The vacuum pump 50 evacuates the chamber 20, for example, to a pressure below 1 Torr, for example, to 1 to 500 mTorr, for example, 50 mTorr.

[0120] These steps (vii) to (ix) may be repeated a number of times set by the production method, for example, two to ten times, for example, six times.

[0121] Next, a second purification cycle is performed. The second purification cycle may be the same as the first purification cycle, or may have a different number of repetitions of steps (iv) to (vi) and / or a different delay time and / or a different pressure.

[0122] The cycle of the first reactant half cycle, the first purge cycle, the second reactant half cycle, and the second purge cycle may be repeated a number of times set by the recipe, for example, one to ten times.

[0123] As described above, the coating process can be performed at a low processing temperature (e.g., below 50°C, for example, at or below 35°C). In particular, during all steps (i) to (ix) described above, the particles can be kept or maintained at such a temperature. Typically, during steps (i) to (ix), the temperature of the interior space of the reactor chamber does not exceed 35°C. This can be achieved by injecting the first reactant gas, the second reactant gas, and the inert gas into the chamber at such a temperature during the corresponding cycle. In addition, if necessary, the physical components of the chamber can be kept or maintained at such a temperature, for example, using a cooling system (e.g., a thermoelectric cooler).

[0124] Process for preparing a pharmaceutical composition comprising a drug encapsulated by one or more layers of metal oxide

[0125] Two exemplary methods for pharmaceutical compositions containing drug-containing cores (ASD particles) encapsulated by one or more metal oxide materials are provided. The first exemplary method includes the following sequential steps: (a) loading drug-containing particles into a reactor, (b) applying a vapor or gaseous metal precursor to a substrate in the reactor, (c) performing one or more pumping and purging cycles of the reactor using an inert gas, (d) applying a vapor or gaseous oxidant to a substrate in the reactor, and (e) performing one or more pumping and purging cycles of the reactor using an inert gas. In some embodiments of the first exemplary method, sequential steps (b) to (e) are repeated one or more times as appropriate to increase the total thickness of the one or more metal oxide materials encapsulating the solid core of the coated particles. In some embodiments, the reactor pressure is stabilized after step (a), step (b), and / or step (d). In some embodiments, the reactor contents are stirred before and / or during step (b), step (c), and / or step (e). In some embodiments, a subset of the vapor or gaseous contents is pumped out before step (c) and / or step (e).

[0126] A second exemplary method includes (e.g., is a combination of) the following sequential steps: (a) loading particles comprising a drug into a reactor, (b) reducing the reactor pressure to less than 1 Torr, (c) stirring the reactor contents until the reactor contents have a desired moisture content, (d) pressurizing the reactor contents to at least 10 Torr by adding a vapor or gaseous metal precursor, (e) stabilizing the reactor pressure, (f) stirring the reactor contents, (g) pumping out a subset of the vapor or gaseous contents and deciding when to stop pumping based on an analysis of the contents in the reactor, the contents including the metal precursor and the particles on the substrate or surface. The method of claim 1, wherein the steps (a) of step (b) to step (m) are: (i) pressurizing the reactor to at least 10 Torr by adding a vapor or gaseous oxidant, (j) stabilizing the reactor pressure, (k) stirring the reactor contents, (i) pumping out a subset of the vapor or gaseous contents, and determining when to stop pumping based on an analysis of the contents in the reactor, the contents including the metal precursor, the byproducts of the metal precursor that react with the exposed hydroxyl residues on the substrate or on the particle surface, and unreacted oxides, and (m) performing a sequence of pumping purge cycles of the reactor using an inert gas. In some embodiments of the second exemplary method, sequential steps (b)-(m) are optionally repeated one or more times to increase the total thickness of the one or more metal oxide materials encapsulating the solid core of the coated particles.

[0127] Some embodiments provide methods for preparing a pharmaceutical composition comprising coated particles, the coated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, the method comprising the following sequential steps: (a) providing uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient (API) and a polymer; (b) performing atomic layer deposition to apply a metal oxide layer to the uncoated particles comprising the amorphous solid dispersion of the active pharmaceutical ingredient and the polymer, thereby preparing coated particles comprising the active pharmaceutical ingredient encapsulated by one or more metal oxide layers; and (c) treating the coated particles to prepare a pharmaceutical composition.

[0128] In some embodiments, the uncoated particles are at least 50% wt / wt API. In some embodiments, the uncoated particles are at least 70% wt / wt API. In some embodiments, the coated particles have a D50 of 0.5 μm to 200 μm based on a spatial average. In some embodiments, the coated particles have a D90 of 200 μm to 2000 μm based on a spatial average.

[0129] In some embodiments, the glass transition temperature of the active pharmaceutical ingredient in the coated particles is higher than the glass transition temperature of the active pharmaceutical ingredient in the provided particles.

[0130] In some embodiments, the polymer is selected from the group consisting of hydroxypropyl methylcellulose, hydroxypropyl methylcellulose acetate succinate (HPMCAS), and polyvinyl pyrrolidone (PVP), polyvinyl pyrrolidone / vinyl acetate, polyethylene glycol (PEG), polyacrylates, and polymethacrylates.

[0131] In some embodiments, step (a) comprises hot melt extrusion. In some embodiments, step (a) comprises spray drying a composition comprising a polymer and an active pharmaceutical ingredient. In some embodiments, the polymer and the active pharmaceutical ingredient are stirred before and / or during step (a).

[0132] In some embodiments, the step of performing atomic layer deposition comprises: (b1) loading particles containing a drug into a reactor; (b2) applying a vapor or gaseous metal precursor to the particles in the reactor; (b3) performing one or more pump-purge cycles of the reactor using an inert gas; (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and (b5) performing one or more pump-purge cycles of the reactor using an inert gas. In some embodiments, before performing step (c), steps (b2) to (b5) are performed two or more times to increase the total thickness of the metal oxide layer.

[0133] In some embodiments, the reactor pressure is stabilized after step (b1), step (b2), and / or step (b4). In some embodiments, the reactor contents are stirred before and / or during step (b1), step (b3), and / or step (b5). In some embodiments, a subset of the vapor or gaseous contents is pumped out before step (b3) and / or (b5). In some embodiments, step (b) occurs at a temperature between 35° C. and 50° C. In some embodiments, step (c) comprises combining the coated particles with one or more pharmaceutically acceptable excipients.

[0134] In some embodiments, the metal oxide layer has a thickness in a range of 0.1 nm to 100 nm.

[0135] In some embodiments, the metal oxide is selected from the group consisting of zinc oxide, aluminum oxide, silicon oxide, and titanium oxide. In some embodiments, the metal oxide is aluminum oxide. In some embodiments, the metal oxide is selected from the group consisting of aluminum oxide and titanium oxide. In some embodiments, the API is selected from the group consisting of ezetimibe, erlotinib, and nifedipine. In some embodiments, the polymer is selected from the group consisting of HPMCAS, PVPVA, and PVP.

[0136] In some embodiments, during storage, the coated particles in step (b) are less prone to agglomeration than the uncoated particles in step (a). In some embodiments, during storage, the coated particles in step (b) remain amorphous for a longer time than the uncoated particles in step (a). In some embodiments, the coated particles in step (b) are less hygroscopic than the uncoated particles in step (a). In some embodiments, during storage, the coated particles in step (b) exhibit slower crystallization than the uncoated particles in step (a).

[0137] Some embodiments provide a pharmaceutical composition comprising coated particles, the coated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, the pharmaceutical composition being prepared by a method comprising the following sequential steps: (a) providing uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient and a polymer; (b) performing atomic layer deposition to apply a metal oxide layer to the uncoated particles comprising the amorphous solid dispersion of the active pharmaceutical ingredient and a polymer, thereby preparing coated particles comprising the active pharmaceutical ingredient encapsulated by one or more metal oxide layers; and (c) treating the coated particles to prepare the pharmaceutical composition.

[0138] In some embodiments, performing atomic layer deposition comprises:

[0139] (b1) loading drug-containing particles into a reactor; (b2) applying a vapor or gaseous metal precursor to the particles in the reactor; (b3) performing one or more pump-purge cycles of the reactor using an inert gas; (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and (b5) performing one or more pump-purge cycles of the reactor using an inert gas.

[0140] In some embodiments, before performing step (c), steps (b2) to (b5) are performed twice or more to increase the total thickness of the metal oxide layer. In some embodiments, the polymer and active pharmaceutical ingredient are stirred before and / or during step (a). In some embodiments, the reactor pressure is stabilized after step (b1), step (b2), and / or step (b4). In some embodiments, before and / or during step (b1), step (b3), and / or step (b5), the reactor contents are stirred. In some embodiments, a subset of the vapor or gaseous contents is pumped out before step (b3) and / or step (b5). In some embodiments, step (b) occurs at a temperature between 35°C and 50°C.

[0141] In some embodiments, the metal oxide layer has a thickness in the range of 0.1 nm to 100 nm. In some embodiments, the uncoated particles have a median particle size based on a spatial average of between 0.1 μm and 1000 μm.

[0142] In some embodiments, the coated particles comprising the active pharmaceutical ingredient further comprise one or more pharmaceutically acceptable excipients. In some embodiments, the uncoated particles consist of the active pharmaceutical ingredient.

[0143] In some embodiments, the metal oxide is selected from the group consisting of aluminum oxide and titanium oxide. In some embodiments, the API is selected from the group consisting of ezetimibe, erlotinib, and nifedipine. In some embodiments, the polymer is selected from the group consisting of HPMCAS, PVPVA, and PVP.

[0144] In some embodiments, during storage, the coated particles in step (b) are less prone to agglomeration than the uncoated particles in step (a). In some embodiments, during storage, the coated particles in step (b) remain amorphous for a longer time than the uncoated particles in step (a). In some embodiments, the coated particles in step (b) are less hygroscopic than the uncoated particles in step (a). In some embodiments, during storage, the coated particles in step (b) exhibit slower crystallization than the uncoated particles in step (a).

[0145] Pharmaceutically acceptable excipients, diluents, and carriers

[0146] Pharmaceutically acceptable excipients include, but are not limited to:

[0147] (1) Surfactants and polymers, including: polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP), sodium lauryl sulfate, polyvinyl alcohol, cross-linked polyvinylpyrrolidone, polyvinyl acrylate copolymer (PVPVA), cellulose derivatives, hydroxypropyl methylcellulose, hydroxypropyl cellulose, carboxymethylethyl cellulose, hydroxypropyl methylcellulose phthalate, polyacrylates and polymethacrylates, urea, sugars, polyols, thickeners and their polymers, emulsifiers, carbohydrate gums, starches, organic acids and their salts.

[0148] (2) Binders, such as cellulose, cross-linked polyvinyl pyrrolidone, and microcrystalline cellulose;

[0149] (3) fillers, such as lactose monohydrate, anhydrous lactose, microcrystalline cellulose, and various starches;

[0150] (4) lubricants, such as agents that affect the flowability of the powder to be compressed, including colloidal silicon dioxide, talc, stearic acid, magnesium stearate, calcium stearate, silica gel;

[0151] (5) sweeteners, such as any natural or artificial sweetener, including sucrose, xylitol, saccharin sodium, cyclamate, aspartame, and acesulfame K;

[0152] (6) flavoring agents;

[0153] (7) preservatives such as potassium sorbate, methylparaben, propylparaben, benzoic acid and its salts, other esters of parabens such as butylparaben, alcohols such as ethanol or benzyl alcohol, phenolic chemicals such as phenol, or quaternary compounds such as benzalkonium chloride;

[0154] (8) Buffer;

[0155] (9) diluents, such as pharmaceutically acceptable inert fillers, such as microcrystalline cellulose, lactose, dibasic calcium phosphate, sugars, and / or mixtures of any of the foregoing;

[0156] (10) Wetting agents such as wheat starch, potato starch, corn starch, and modified starches, and mixtures thereof;

[0157] (11) disintegrants such as croscarmellose sodium, crospovidone, sodium starch glycolate; and

[0158] (12) Effervescent agents, such as effervescent couples, such as organic acids (e.g., citric acid, tartaric acid, malic acid, fumaric acid, adipic acid, succinic acid, and alginic acid and anhydrides and acid salts), or carbonates (e.g., sodium carbonate, potassium carbonate, magnesium carbonate, sodium glycine carbonate, L-lysine carbonate and arginine carbonate) or bicarbonates (e.g., sodium bicarbonate or potassium bicarbonate).

[0159] Examples

[0160] The following materials and methods were used in the Examples.

[0161] To apply the aluminum oxide coating, the vapor or gaseous metal precursor is trimethylaluminum (TMA), which forms byproduct gaseous methane upon reaction of TMA with exposed hydroxyl groups on the particle or on the surface of the coated particle, and the oxidant is water vapor.

[0162] ALD coating method

[0163] In short, for the production of Al 2 C 3 The coating method comprises the following sequential steps:

[0164] (a) loading particles containing a drug into a reactor;

[0165] (b) reducing the reactor pressure to less than 1 Torr;

[0166] (c) stirring the reactor contents until the reactor contents have a desired water content by performing a residual gas analysis (RGA) to monitor the level of water vapor in the reactor;

[0167] (d) pressurizing the reactor to at least 1 Torr by adding steam or gaseous TMA;

[0168] (e) stabilizing the reactor pressure;

[0169] (f) stirring the reactor contents;

[0170] (g) pumping out a subset of the vapor or gaseous contents including gaseous methane and unreacted TMA, and deciding when to stop pumping by performing an RGA to monitor the levels of gaseous methane and unreacted TMA in the reactor;

[0171] (h) performing a sequence of pump-purge cycles on the reactor using nitrogen;

[0172] (i) pressurizing the reactor to at least 1 Torr by adding water vapor;

[0173] (j) stabilizing the reactor pressure;

[0174] (k) stirring the reactor contents;

[0175] (I) pumping out a subset of the vapor or gaseous contents including water vapor, and determining when to stop pumping by performing an RGA to monitor the level of water vapor in the reactor; and

[0176] (m) A sequence of pump-purge cycles using nitrogen gas was performed on the reactor.

[0177] In some cases, steps (b) to (m) are repeated more than once to increase the total thickness of the metal oxide encapsulating the drug particle core. 2 The coating can be achieved by using TiCl 4 is applied by a similar process.

[0178] Example 1: Metal oxide coated ASD particles resist crystallization, exhibit less agglomeration and have improved compressibility and flowability compared to uncoated ASD particles

[0179] Particles of ASD with ezetimibe in hydroxypropylmethylcellulose acetate succinate (HPMCAS) with 50% or 70% drug loading were prepared by spray drying. Particles with 50% (B3-140 and B3-141) or 70% (B3-139A, B3-138B and B3-139B) drug loading were coated with alumina by ALD at 35°C essentially as described above. The ASD particles received a coating of about 5 nm thick (B3-140 and B3-139A), about 15 to 20 nm thick (B3-138B) or about 20-30 nm thick (B3-141 and B3-139B). The particle size distribution of various ASD particles is shown in Table 1.

[0180]

[0181] Table 1

[0182] X-ray diffraction was used to evaluate the coated and uncoated ASD particles. Figure 2 As shown, x-ray diffraction analysis showed that the coated and uncoated ASD particles were amorphous. Thermal analysis was used to evaluate the glass transition temperature (Tg) and thermally induced crystallization of the coated and uncoated ASD particles. Figure 3 As can be seen in the Figure 5, the coated ASD particles exhibit a higher glass transition temperature (Tg) than the uncoated ASD particles. As can also be seen, the coating significantly reduces thermally induced crystallization, especially for the ASD particles with 70% drug loading.

[0183] Scanning electron microscopy was used to evaluate the morphology of the coated and uncoated ASD particles. Figure 4As can be seen in the Figure 3, the coated ASD particles are less agglomerated than the uncoated ASD particles.

[0184] The compressibility and flowability of coated and uncoated ASD particles were measured. Figure 5 As can be seen in Figure 5, the coating improves the compressibility and flowability of the ASD particles.

[0185] Isothermal moisture sorption was used to evaluate the hygroscopic tendencies of coated and uncoated ASD particles. Figure 6 As can be seen in Figure 5, the coated ASD particles are less hygroscopic than the uncoated ASD particles.

[0186] Example 2: Metal oxide coated ASD particles resist crystallization under accelerated stability study conditions

[0187] The coated and uncoated ASD particles of Example 1 were subjected to an accelerated stability study. The coated and uncoated ASD particles were stored at 40°C / 75% relative humidity. Samples of the coated and uncoated ASD particles were analyzed by x-ray diffraction at days 12, 19, 26, 33, 40, 47, 54, and 61. As can be seen in Figure 7 As can be seen in Figure 5, the uncoated ASD particles became gradually crystalline, especially the 70% drug loaded ASD particles, while the coated ASD particles remained essentially amorphous. Figure 8 Only the x-ray diffraction data of the uncoated ASD particles are presented. The increased crystallinity of these ASF particles can be more easily seen here.

[0188] Thermal analysis was used to evaluate thermally induced crystallization of coated and uncoated ASD particles subjected to accelerated stability studies. Fig. 9 As can be seen in FIG. 1 , the coated ASD sample appears to have a higher glass transition temperature (Tg) than the uncoated ASD sample. Fig. 9 As can be seen in Figure 5, even at 50% drug loading, the uncoated ASD particles exhibited thermally induced crystallization after only one month. Even after 2 months, the coated ASD particles exhibited little change in thermally induced crystallization.

[0189] Scanning electron microscopy was used to evaluate the morphology of the coated and uncoated ASD particles. FIG. 10A to FIG. 10B and FIG. 11A to FIG. 11B As seen in Figure 5, crystals were visible on the surface of uncoated 50% drug-loaded ASD particles at day 17 and on uncoated 70% drug-loaded ASD particles at day 12. In contrast, under accelerated stability conditions, crystals were not visible on the surface of coated ASD particles even after 61.

[0190] The coated and uncoated ASD particles (alumina / ezetimibe / HPMCAS) of Example 1 were subjected to an accelerated stability study under open conditions (storage for 8 months at 40°C and 75% relative humidity). Fig.14 As can be seen in the figure, the uncoated ASD particles (50% and 70% drug loading) show a darker color (yellow) compared to the coated ASD particles. In addition, the uncoated ASD (50% and 70% drug loading) shows more agglomeration compared to the thinly coated ASD (B3-139A). The intermediate coated ASD (B3-139B) and thickly coated ASD (B3-141 and B3-139B) do not have agglomeration.

[0191] The samples were also evaluated by scanning electron microscopy (SEM) to evaluate the particle morphology of uncoated and metal oxide coated 50% DL (drug loaded) ASD particles (alumina / ezetimibe / HPMCAS) after storage at 40°C and 75% relative humidity for different time periods (12 days, 47 days, 210 days, 240 days and 270 days). Fig.15 As shown, while crystallization started before day 47 for the uncoated ASD, there was no crystallization for the ALD coated ASD (50% B3-140 and 50% B3-141) during the 9-month storage duration.

[0192] The samples were also evaluated by scanning electron microscopy (SEM) to evaluate the particle morphology of uncoated and metal oxide coated 70% DL ASD particles (alumina / ezetimibe / HPMCAS) after storage at 40°C and 75% relative humidity for different time periods (12 days, 61 days, 180 days, 210 days, 240 days and 270 days). Fig.16 As shown, while crystallization started as early as day 12 for the uncoated ASD, for the thinly coated ASD (70% B3-139A), there was no crystallization until 7 months (day 210), and for the thickly coated ASD (70% B3-138B and 70% B3-139B), there was no crystallization during the 9-month storage duration.

[0193] After storage for 9 months at 40°C and 75% relative humidity, samples of coated and uncoated ASD particles (alumina / ezetimibe / HPMCAS) were analyzed by x-ray diffraction. Fig.17 As shown, there is about 25% crystallinity for the uncoated ASD with 50% API loading, about 50% crystallinity for the uncoated ASD with 70% API loading, and no crystallinity for most of the coated samples.

[0194] The samples were also evaluated by scanning electron microscopy (SEM) to assess the particle morphology of uncoated and metal oxide coated ASD particles (alumina / ezetimibe / HPMCAS) after storage for one year at 40°C and 75% relative humidity. Fig.19 As shown, both 50% and 70% uncoated ASD were completely crystallized. For the 50% DL coated sample, no crystallization was present. For the 70% coated ASD, a small amount of crystallization was observed.

[0195] After storage for one year at 40°C and 75% relative humidity, samples of coated and uncoated ASD particles (alumina / ezetimibe / HPMCAS) were analyzed by x-ray diffraction. Fig. 20 As shown, there is significant crystallization for both 50% and 70% uncoated ASD, a small amount of crystallization for the 70% thinly coated ASD (B3-139A), and close to zero crystallization for most of the other coated samples.

[0196] Example 3: Metal oxide coated ASD particles resist degradation of API release

[0197] Crystallization reduces the solubility of ezetimibe. The release of ezetimibe from coated and uncoated ASD particles prepared as described in Example 1 was studied. In each case, the dissolution conditions were 37°C, stirring at 200 rpm in 50 ml of phosphate buffer in FaSSSIF (pH 6.5) solution, and the amount of ASD particles used was equivalent to 10 mg of ezetimibe. Therefore, the maximum possible concentration of ezetimibe in this release study was 200 μg / ml. After adding ASD particles equivalent to 10 mg of ezetimibe, release curve data were collected by real-time in situ UV dissolution measurement. As can be seen in Fig.12 As can be seen in Figure 5, after 1 month at 40°C / 75% relative humidity, the release rate of ezetimibe from the uncoated 50% drug-loaded ASD particles was greatly reduced. In contrast, the release rate from the coated 50% drug-loaded ASD particles was almost unchanged. As can be seen in Figure 5, Fig.13 As can be seen in Figure 2, after 1 month at 40°C / 75% relative humidity, the release rate of ezetimibe from the uncoated 70% drug-loaded ASD particles was greatly reduced. In contrast, the release rate from the coated 70% drug-loaded ASD particles was almost unchanged. The reduced release from the uncoated particles may be attributed to the increase in crystallinity and agglomeration over time. Fig.18 As shown, the C of the uncoated sample max (maximum serum concentration) decreased during the 9-month storage duration, whereas for the coated samples, C maxis quite stable. In addition, the T max (Observed C max The time of storage increases significantly after one month, possibly due to agglomeration or wetting. Fig.21A and Fig. 21B As shown, ALD coating did not have any negative impact on the release profile of ezetimibe. After storage for one month or longer, the coated ASD particles showed better release, probably because the coated ASD particles maintained the amorphous state of the API. Here, the solubility of crystalline ezetimibe was 0.8+ / -0.3ug / mL, and the solubility of amorphous ezetimibe was 20.2+ / -0.4ug / ml.

[0198] Example 4: Alumina-coated Erlotinib HPMCAS ASD particles with 60% drug loading (Alumina / Erlotinib / HPMCAS)

[0199] Particles of ASD with 60% drug loading of erlotinib in hydroxypropylmethylcellulose acetate succinate (HPMCAS) were prepared by spray drying. Particles EH60-5 were coated with alumina by ALD at 35°C essentially as described above. EH60-5 is an uncoated ASD particle with 60% drug loading (erlotinib / HPMCAS). B3-281B is a coated ASD particle with 60% drug loading (alumina / erlotinib / HPMCAS).

[0200] Freshly prepared uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading were tested for powder flowability. Fig.23 As shown, based on the powder flow characterization of uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading, the coated ASD particles showed higher conditioned bulk density (CBD) compared to the uncoated ASD particles. Fig.23 As shown, the compressibility measured by the percent spatial change after compression at 15 kPa (CPS@15 kPa) is lower in the coated ASD compared to the uncoated ASD. Fig.23 As shown, the flow functional coefficient after compression at 3 kPa (FFc@3 kPa) is higher in the coated ASD compared to the uncoated ASD, thereby improving the bonded ASD powder to the easy-flowing region.

[0201] Freshly prepared uncoated and coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading were analyzed by x-ray diffraction. Fig.24 As shown, there is no crystallization after coating based on x-ray diffraction analysis of uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading.

[0202] Freshly prepared uncoated and coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading were also analyzed by Fourier transform infrared spectroscopy. Fig.25A and Fig.25B As shown, based on FTIR analysis of uncoated and metal oxide coated ASD particles (alumina / erlotinib / HPMCAS) with 60% drug loading, the FTIR spectra did not change after coating.

[0203] Example 5: Alumina-coated Erlotinib PVPVA ASD particles with 50% drug loading (Alumina / Erlotinib / PVPVA)

[0204] Particles of ASD with 50% drug loading of erlotinib in polyvinyl pyrrolidone-polyvinyl acrylate copolymer (PVPVA) were prepared by spray drying with the following parameters: 1) input / output temperature: 105°C / 68°C; 2) spray flow rate (setting): 20%; 3) aspirator: 100%; and 4) gas flow: 55. EP50-15 is an uncoated ASD particle with 50% drug loading (erlotinib / PVPVA). B3-284A is a thinly coated ASD particle with 50% drug loading (alumina / erlotinib / PVPVA). B3-284B is a thickly coated ASD particle with 50% drug loading (alumina / erlotinib / PVPVA).

[0205] Freshly prepared thin-coated ASD (B3-284A) and thick-coated ASD (B3-284B) were analyzed to evaluate coating thickness and oxide content. Fig.26A As shown, the thin-coated ASD (B3-284A) has a coating thickness of about 4.4 to 5.5 nm, and the thick-coated ASD (B3-284B) has a coating thickness of about 8.8 to 9.4 nm. The thin-coated ASD (B3-284A) has an oxide content of about 1.6%, and the thick-coated ASD (B3-284B) has an oxide content of about 3.31%.

[0206] Isothermal moisture sorption was used to evaluate the hygroscopic tendencies of coated and uncoated ASD particles. Fig. 27 As can be seen in , the uncoated and coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading have comparable isotherms.

[0207] Samples of uncoated and coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading stored in open bottles at 40°C and 43% relative humidity for 4 weeks were analyzed by x-ray diffraction. Fig.28 As shown, while the uncoated ASD particles (EP50-15) began to crystallize within about 2 to 3 weeks, no crystallization was observed for the coated ASD particles (B3-284A and B3-284B).

[0208] Samples of uncoated and coated ASD particles (alumina / erlotinib / PVPVA) with 50% drug loading stored in open bottles at 40°C and 43% relative humidity for 4 weeks were also analyzed by SEM. Fig.29 As shown, while the uncoated ASD particles (EP50-15) began to crystallize within about 1 to 2 weeks, no crystallization was observed for the coated ASD particles (B3-284A and B3-284B).

[0209] Example 6 Metal oxide coated nifedipine PVP ASD with 50% and 70% drug loading (aluminum oxide / nifedipine / PVP or titanium oxide / nifedipine / PVP)

[0210] Particles of ASD with 50% (SF20000521) or 70% (SF20000611) nifedipine in polyvinylpyrrolidone (PVP) were prepared by spray drying according to Table 2. Particles were coated with alumina by ALD at 35°C essentially as described above.

[0211]

[0212] Table 2

[0213] The particle size distribution, bulk density and tap density of various uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading are shown in Table 3.

[0214]

[0215] Table 3

[0216] Freshly prepared uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading were analyzed for nifedipine content and water content. Fig. 30AAs shown, the uncoated granules (SF20000521A and SF20000611A) have a higher nifedipine content and a higher water content than the coated granules (SF20000521B and SF20000611B).

[0217] like Fig.31 As shown, visual inspection of freshly prepared uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings showed no significant agglomeration.

[0218] Freshly prepared uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading were analyzed by x-ray diffraction. FIG. 32A to FIG. 32F As shown, no crystallization is present.

[0219] Uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% and 70% drug loading were subjected to moisture sorption analysis after storage for various durations in capped amber glass bottles, capped induction sealed HDPE bottles, and open HDPE bottles without caps. FIG. 33A to FIG. 33B As shown, for the 50% drug loaded sample (SF20000521), the coated ASD particles showed less impurities compared to the uncoated ASD particles after storage under various conditions. FIG. 33C to FIG. 33D As shown, for the 70% drug loading sample (SF20000611), there are comparable impurity and moisture contents for the coated and uncoated ASD particles.

[0220] Samples of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored for various durations in open HDPE bottles without caps at 40°C and 75% relative humidity were subjected to visual inspection. Fig.34 As shown, the uncoated ASD with 50% drug loading (SF20000521A) and 70% drug loading (SF20000611A) showed significant agglomeration (clump formation) and color change. After 3 months, no agglomeration was observed for the coated ASD with 50% drug loading (SF20000521B) and 70% drug loading (SF20000611B).

[0221] Samples of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading stored for various durations in induction sealed HDPE bottles with caps were subjected to visual inspection. Fig.35 As shown, the uncoated ASD with 50% drug loading (SF20000521A) and 70% drug loading (SF20000611A) showed significant agglomeration (clump formation). For the coated ASD with 50% drug loading (SF20000521B) and 70% drug loading (SF20000611B), no agglomeration was observed.

[0222] Samples of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loadings stored for various durations in capped amber bottles were subjected to visual inspection. Fig.36 As shown, the uncoated ASD with 50% drug loading (SF20000521A) and 70% drug loading (SF20000611A) showed significant agglomeration (clump formation). After three months, no agglomeration was observed for the coated ASD with 50% drug loading (SF20000521B) and 70% drug loading (SF20000611B).

[0223] Samples of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading stored in capped amber bottles at 25°C and 60% relative humidity for 3 months were subjected to X-ray diffraction analysis. Fig.37 As shown, no crystallization was observed for either the coated or uncoated samples.

[0224] Samples of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading stored for 3 months at 40°C and 75% relative humidity in induction sealed HDPE bottles with caps were subjected to X-ray diffraction analysis. Fig.38 As shown, for the 70% drug loaded samples, there is significant crystallization in the uncoated sample (20000611A) and no crystallization in the coated sample (20000611B).

[0225] Samples of uncoated and metal oxide coated ASD particles (alumina / nifedipine / PVP) with 50% (SF20000521) and 70% (SF20000611) drug loading stored in open HDPE bottles without caps for 3 months at 40°C and 75% relative humidity were subjected to X-ray diffraction analysis. Fig.39 As shown, for the 50% and 70% drug loaded samples, there is significant crystallization in the uncoated samples (20000521A and 20000611A) and a relatively smaller amount of crystallization in the coated samples (20000521B and 20000611B).

[0226] The samples were also evaluated by scanning electron microscopy (SEM) to assess the particle morphology of uncoated and metal oxide coated ASD particles (alumina / nifedipine / HPMCAS) with 50% (SF20000521) and 70% (SF20000611) drug loading after storage for 3 months at 40°C and 75% relative humidity in open HDPE bottles without caps. Fig.40A As shown, uncoated 50% and 70% drug loaded ASD particles showed significant crystallization (complete gelation) after storage in an open bottle for 3 months. In fact, SEM images were taken after grinding / crushing the samples into small pieces due to agglomeration. In contrast, FIG. 40B to FIG. 40C As shown, the coated 50% and 70% drug loaded ASD particles showed no crystallization or morphology changes after storage in an open bottle for 3 months.

Claims

1. A method for preparing a pharmaceutical composition comprising coated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, the method comprising the following sequential steps: (a) providing uncoated particles comprising an amorphous solid dispersion (ASD) of an active pharmaceutical ingredient (API) and a polymer, wherein the uncoated particles are at least 50% wt / wt API; (b) performing atomic layer deposition to apply a metal oxide layer to uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient and a polymer, thereby preparing coated particles comprising an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, wherein the ASD of the coated particles has a greater glass transition temperature than the ASD of the uncoated particles; and (c) processing the coated particles to prepare a pharmaceutical composition.

2. The method of claim 1, wherein the uncoated particles are at least 60% wt / wt API.

3. The method of claim 2, wherein the uncoated particles are at least 70% wt / wt API.

4. The method of claim 1, wherein the coated particles have a D50 of 0.5 μm to 200 μm based on a spatial average.

5. The method of claim 4, wherein the coated particles have a D90 based on a spatial average of 200 μm to 2000 μm.

6. The method of claim 1, wherein the glass transition temperature of the active pharmaceutical ingredient in the coated particles is higher than the glass transition temperature of the active pharmaceutical ingredient in the provided particles.

7. The method of claim 1, wherein the polymer is selected from the group consisting of hydroxypropyl methylcellulose, hydroxypropyl methylcellulose acetate succinate (HPMCAS), polyvinyl pyrrolidone (PVP), polyvinyl pyrrolidone / vinyl acetate, polyethylene glycol (PEG), polyacrylates, and polymethacrylates.

8. The method of claim 1, wherein the step of performing atomic layer deposition comprises the following steps: (b1) loading the particles containing the drug into a reactor; (b2) applying a vapor or gaseous metal precursor to the particles in the reactor; (b3) performing one or more pump-purge cycles of the reactor using an inert gas; (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and (b5) performing one or more pump-purge cycles of the reactor using an inert gas.

9. The method of claim 1, wherein the metal oxide is selected from the group consisting of zinc oxide, aluminum oxide, silicon oxide, and titanium oxide.

10. The method of claim 9, wherein the metal oxide is aluminum oxide.

11. The method of claim 1, wherein step (b) occurs at a temperature between 25°C and 50°C.

12. The method of claim 1, wherein the coated particles consist of: Amorphous solid dispersions of active pharmaceutical ingredients and coatings composed of metal oxides.

13. The method of claim 1, wherein the API is selected from the group consisting of ezetimibe, erlotinib, and nifedipine.

14. The method of claim 1, wherein the polymer is selected from the group consisting of HPMCAS, PVPVA, and PVP.

15. The method of claim 1, wherein during storage, the coated particles in step (b) are less prone to agglomeration than the uncoated particles in step (a); and / or wherein during storage, the coated particles in step (b) remain amorphous for a longer time than the uncoated particles in step (a); and / or wherein during storage, the coated particles in step (b) exhibit slower crystallization than the uncoated particles in step (a).

16. The method of claim 1, wherein the uncoated particles are 50%-70% wt / wt API.

17. A method of reducing the crystallization rate in a pharmaceutical composition comprising coated particles, the coated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient, the method comprising the steps of: (a) providing uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient (API) and a polymer, wherein the uncoated particles are at least 50% wt / wt API; (b) performing atomic layer deposition to apply a metal oxide layer to uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient and a polymer, thereby preparing coated particles comprising an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, wherein the ASD of the coated particles has a greater glass transition temperature than the ASD of the uncoated particles; and (c) processing the coated particles to prepare a pharmaceutical composition.

18. The method of claim 17, wherein the uncoated particles are 50%-70% wt / wt API.

19. A pharmaceutical composition comprising coated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, the pharmaceutical composition being prepared by a process comprising the following sequential steps: (a) providing uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient and a polymer, wherein the uncoated particles are at least 50% wt / wt API; (b) performing atomic layer deposition to apply a metal oxide layer to uncoated particles comprising an amorphous solid dispersion of an active pharmaceutical ingredient and a polymer, thereby preparing coated particles comprising an active pharmaceutical ingredient encapsulated by one or more metal oxide layers, wherein the ASD of the coated particles has a greater glass transition temperature than the ASD of the uncoated particles; and (c) processing the coated particles to prepare a pharmaceutical composition.

20. The composition of claim 19, wherein the step of performing atomic layer deposition comprises the following steps: (b1) loading the particles containing the drug into a reactor; (b2) applying a vapor or gaseous metal precursor to the particles in the reactor; (b3) performing one or more pump-purge cycles of the reactor using an inert gas; (b4) applying a vapor or gaseous oxidant to the particles in the reactor; and (b5) performing one or more pump-purge cycles of the reactor using an inert gas.

21. The composition of claim 19, wherein the coated particles comprising an active pharmaceutical ingredient further comprise one or more pharmaceutically acceptable excipients.

22. The composition of claim 19, wherein the uncoated particles have a median particle size based on a spatial average of between 0.1 μm and 1000 μm.

23. The composition of claim 19, wherein the API is selected from the group consisting of ezetimibe, erlotinib and nifedipine.

24. The composition of claim 19, wherein the polymer is selected from the group consisting of HPMCAS, PVPVA and PVP.

25. The composition of claim 19, wherein during storage, the coated particles in step (b) are less prone to agglomeration than the uncoated particles in step (a); and / or wherein during storage, the coated particles in step (b) remain amorphous for a longer time than the uncoated particles in step (a); and / or wherein during storage, the coated particles in step (b) exhibit slower crystallization than the uncoated particles in step (a).

26. The pharmaceutical composition of claim 19, wherein the uncoated particles are 50%-70% wt / wt API.

Citation Information

Patent Citations

  • A Method of Preparing Amorphous Solid Dispersion in Submicron Range by Co-Precipitation

    US20170209372A1

  • Metal Oxide Encapsulated Drug Compositions and Methods of Preparing the Same

    US20190216742A1